A simplified structure for three‐phase 4‐level inverter employing fundamental frequency switching technique. Issue 14 (1st November 2017) - Masaoud, Ammar; Mekhilef, Saad; Wooi Ping, Hew; Ing Wong, Kiing
Abstract : This study describes the design and control of simplified structure of three‐phase 4‐level inverter. A 4‐level dc‐link derived from three symmetrical dc voltage supplies and two controlled switches is connected to a three‐phase 3‐level neutral point clamped (3‐level NPC) bridge inverter. By employing the fundamental frequency switching technique, the simplified 4‐level inverter can have two distinct modes of operation: 4‐level and 2‐level. Compared to the well‐known three‐phase 4‐level NPC inverter, the proposed inverter topology comes with series of features including a minimum number of power components, high quality voltage waveform, lower losses and higher efficiency. To ensure the feasibility of the proposed topology with its suggested modulation technique, the prototype of the proposed 4‐level inverter is built and the experimental results are given.